Pachychoroid spectrum - Khunsongkiet, Preeyanuch; Patikulsila, Direk; Choovuthayakorn, Janejit; Watanachai, Nawat; Kunavisarut, Paradee; Chaikitmongkol, Voraporn (Biomedical Sciences and Clinical Medicine, 2017)
Objective Recently, “pachychoroid spectrum” was proposed as a group of macular diseases with abnormally increased choroidal thickness coexisting with dilated hyperpermeable outer choroidal vessels or “pachyvessels”. The patients were asymptomatic when only thick choroid was found. On the other hand, the vision could be lessened if serous retinal detachment, exudates or submacular hemorrhage presented. Multimodal imaging tools should be used to differentiate these diseases from others that presented with the similar clinical features but different natural courses and treatment response.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">